Tolerance and nutrients consumption of Chlorella vulgaris growing in mineral medium and real wastewater under laboratory conditions - María de Lourdes Franco Martínez; María Dolores Josefina Rodríguez Rosales; Cuauhtémoc Ulises Moreno Medina; Alfredo de Jesús Martínez Roldán (Open Agriculture, 2017)
Microalgae have the potential of consuming high amounts of nitrogen and phosphorus from wastewater; thus, avoiding the risk of eutrophication of the water bodies. Nevertheless, ammonium can usually inhibit the growth of microalgae. Tolerance to ammonium is specific of each strain; so, the development of tertiary wastewater treatment proposals, employing microalgae, has as a first step the study of its tolerance to N-NH3. In this work, the tolerance of Chlorella vulgaris to N-NH3, using mineral medium, was studied. Afterward, C. vulgaris was used to remove nitrogen and phosphorus from a real wastewater. The maximal biomass concentration was reached at 66 ppm N-NH3 (0.49 gL-1) with the complete depletion of the ammonium and a phosphorus consumption of 2 mgPi L-1d-1 in all the experiments. When C. vulgaris was grown in real wastewater, the final biomass concentration was 0.267 g L-1 and the nutrients (N and P) were totally consumed after 3 days. According with these results, this strain of Chlorella has the potential for the removal of nitrogen and phosphorus from tertiary wastewater and the biomass produced in the process can be used for the production of high value products, such as pigments, proteins, carbohydrate or used for animal feed.